Perceptions of Attractive and Healthy-Looking Lips. Issue 2 (March 2019) - Hwang, Kun; Kim, Young Suk; Kim, Hun
Abstract : Abstract: The aim of this study was to characterize Koreans' perceptions of attractive and healthy-looking lips. A survey was conducted among 258 women and 72 men who were asked to view illustrations of various examples of the 4 lip-related ratios (lip thickness-to-width ratio [LTW]; upper-to-lower vermillion ratio [ULR]; upper vermillion thickness-to-upper lip height ratio [VUL]; and lip-to-nose width ratio [LNW]) and to choose which they thought were attractive or healthy-looking. The LTW ratios most often identified as attractive were LTW-1/3 (lip thickness is 1/3 of lip width, 40.0%) and LTW-2/5 (47.3%). The LTW value most often identified as healthy-looking was LTW-2/5 (54.3%). The most attractive ULR ratio was ULR-4/5 (upper vermillion thickness is 4/5 of the lower vermillion, 49.4%). The most healthy-looking ULR ratio was ULR-4/5 (47.0%). The most attractive VUL ratio was VUL-1/2 (thickness of the upper vermillion is 1/2 of upper lip height, 60.3%). The most healthy-looking VUL ratio was VUL-1/2 (61.0%). The most attractive LNW ratio was LNW-3/2 (lip width is 3/2 of nose width, 42.1%). LNW-3/2 was also the most preferred in all age groups below 50 years, while those over 50 preferred LNW-4/3 (55.0%). The most healthy-looking LNW ratios were LNW-3/2 (35.2%) and LNW-4/3 (32.1%). LNW-3/2 was the most preferred in all age groups below 50, while those over 50 preferred LNW-4/3 (40.0%). It therefore seems that older people preferred a narrower lip width than younger people. The results of this study can be applied in lip augmentations or aesthetic lip surgery.